Factors associated with awareness of and undergoing Pap smear tests among Jordanian women - Annab, Abeer; Lataifeh, Lujain; Lataifeh, Isam; Al-Rabadi, Diala; Alkouri, Osama; Khader, Yousef S. (Narra Sains Indonesia, 2024)
Several screening methods are used to detect cervical cancer, with Pap smear test is considered as one of the most reliable screening methods to diagnose cervical cancer. The aim of this study was to investigate the factors associated with awareness of undergoing Pap smear tests among Jordanian women. A cross-sectional study was conducted among 525 Jordanian women attending the outpatient maternity hospital consecutively from February to July 2023. Data encompassed demographic characteristics (age, occupation, and education), awareness of Pap smears, beliefs regarding their importance, sources of information, and the history of undergoing Pap smear tests were collected using a structured questionnaire. Of the total 525 Jordanian women, 87.6% were aware of Pap smears. The awareness varied significantly depending on age and education level. Women aged 41–50 (adjusted odds ratio (AOR): 6.0; 95%CI: 2.3–15.3) and with a university education (AOR: 2.6; 95%CI: 1.4–4.8) were associated with increased odds of being aware of Pap smears. Among the women who were aware of Pap smears, the majority (94.1%) expressed belief in the importance of undergoing Pap smear tests and 61.7% reported having undergone the procedure at least once in their lives. In the multivariate analysis, women aged 30–40 years (AOR: 1.7; 95%CI: 1.1–2.8), 41–50 years (AOR: 4.1; 95%CI: 2.3–7.3), and older than 50 years (AOR: 9.8; 95%CI: 4.2–23.0) had a higher likelihood of undergoing Pap smear tests than those of under 30 years old. Being a housewife (AOR: 1.7; 95%CI: 1.1–2.7) and those who believed in the importance of Pap smear testing (AOR: 2.6; 95%CI: 1.1–6.0) were also more likely to have a Pap smear test. Nearly half of the women who had undergone Pap smears reported doing so every 2–3 years, while 25.7% indicated annual screening. Importantly, the overwhelming majority (97.9%) preferred the procedure to be performed by a gynecologist. In conclusion, the majority of women were aware of Pap smears. Two-thirds of women reported having undergone the procedure at least once. Prevention programs targeting cervical cancer and Pap smear tests should be tailored to women with low education, younger than 30 years, and those employed to maximize screening uptake for cervical cancer.